2022
DOI: 10.1371/journal.pone.0273278
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of web-based intervention for life-change adaptation in family caregivers of community-dwelling individuals with acquired brain injury: A cluster-randomized controlled trial

Abstract: Objective To test the effectiveness of the web-based intervention “Koji-family.net 3-day program” (KF3 PGM) for life-change adaptation in family caregivers of community-dwelling individuals with acquired brain injury (ABI). Design A cluster-randomized trial. Settings All 82 institutions for families of individuals with ABI in Japan. Participants Participants were 240 families at 16 different institutions for families of individuals with ABI. Inclusion criteria for participants were (1) families caring fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Most studies reported a qualitative study design (n � 58) [17,18,21,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] and , followed by mixed methods (n � 9) [95][96][97][98][99][100][101][102][103] and quantitative designs (n � 3) [22,104,105]. Data collection methods consisted of semistructured interviews alone (n � 36) [17, 41-44, 46, 48, 52, 53, 56, 58, 59, 61-65, 67, 69, 70, 72, 76, 78-81, 83-85, 88, 89, 92, 93, 104] or interviews combined with focus groups [77,98], surveys [22,95,96,[99][100][101][102][103], participant observations [49,51,…”
Section: Study Design and Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies reported a qualitative study design (n � 58) [17,18,21,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] and , followed by mixed methods (n � 9) [95][96][97][98][99][100][101][102][103] and quantitative designs (n � 3) [22,104,105]. Data collection methods consisted of semistructured interviews alone (n � 36) [17, 41-44, 46, 48, 52, 53, 56, 58, 59, 61-65, 67, 69, 70, 72, 76, 78-81, 83-85, 88, 89, 92, 93, 104] or interviews combined with focus groups [77,98], surveys [22,95,96,[99][100][101][102][103], participant observations [49,51,…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…Data collection methods consisted of semistructured interviews alone (n � 36) [17, 41-44, 46, 48, 52, 53, 56, 58, 59, 61-65, 67, 69, 70, 72, 76, 78-81, 83-85, 88, 89, 92, 93, 104] or interviews combined with focus groups [77,98], surveys [22,95,96,[99][100][101][102][103], participant observations [49,51,54,55,57,60,66,68,71,73,97], document analysis (i.e., feld notes and medical records) [50,54,66,74,86,96,101], and photographs (i.e., photovoice) [86,90]. Several studies used only focus groups [18,91], analysis of institutional medical records [47], questionnaires [105], and participant observation methods [94]. Te data collection method applied in three studies was not reported [45,82,87].…”
Section: Study Design and Methodsmentioning
confidence: 99%
See 3 more Smart Citations